Convergence of Inflammatory Pathways in Allergic Asthma and Sickle Cell Disease - Samarasinghe, Amali E.; Rosch, Jason W. (Frontiers in Immunology, 2020)
The underlying pathologies of sickle cell disease and asthma share many characteristics in terms of respiratory inflammation. The principal mechanisms of pulmonary inflammation are largely distinct, but activation of common pathways downstream of the initial inflammatory triggers may lead to exacerbation of both disease states. The altered inflammatory landscape of these respiratory pathologies can differentially impact respiratory pathogen susceptibility in patients with sickle cell disease and asthma. How these two distinct diseases behave in a comorbid setting can further exacerbate pulmonary complications associated with both disease states and impact susceptibility to respiratory infection. This review will provide a concise overview of how asthma distinctly affects individuals with sickle cell disease and how pulmonary physiology and inflammation are impacted during comorbidity.